(untitled) (Scientific journal of the Fergana State University, 2024)
A headline is a short, catchy headline or summary that appears at the top of an article, news story, web page, or advertisement. Headings are designed to quickly convey the main idea or key information in the following content, pique the reader’s interest and encourage them to continue reading.